Effective moment of inertia of reinforced concrete slender beams with only tension reinforcement - Olanitori LM; Oniyide MM; Oni ST; Otuaga MP (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2023)
For a reinforced concrete structure to be deemed satisfactory, it must satisfy both the ultimate and serviceability limits state criteria. Deflection is one of the major criteria to be satisfied under the serviceability limit state. This paper derived a model by modifying Olanitori's model to obtain the effective moment of inertia for slender beams without compression reinforcement. The beam without compression reinforcement was subjected to a one-point load in order to determine the experimental effective moment of inertia. It was observed that the beam had an ultimate load of 83 kN. At a service load of 55.33 kN, the beam's actual deflection was found to be 5.90 mm and the experimental effective moment of inertia, Ie(EXP) was 206.96 x104mm4. At a service load of 55.33 kN, the estimated deflections of the beam using the proposed model P, model 1, model 2, and model 3 were 3.32 mm, 2.60 mm, 1.33 mm, and 0.78 mm respectively, while the actual deflection was 5.09 mm for the beam. From these results, the proposed model predicts more accurately the deflection of the slender beam than the three other models.